Sedimentology of a Middle Jurassic Base-of-Slope environment, Cutri Formation, Mallorca - Kettle, Simon Paul (Journal of Iberian Geology, 2016)
The Cutri Formation’s, type location, exposed in the NW of Mallorca, Spain has previously been described by Álvaro et al., (1989) and further interpreted by Abbots (1989) unpublished PhD thesis as a base-of-slope carbonate apron. Incorporating new field and laboratory analysis this paper enhances this interpretation. From this analysis, it can be shown without reasonable doubt that the Cutri Formation was deposited in a carbonate base-of-slope environment on the palaeowindward side of a Mid-Jurassic Tethyan platform. Key evidence such as laterally extensive exposures, abundant deposits of calciturbidtes and debris flows amongst hemipelagic deposits strongly support this interpretation.